ICT for communication - Postigo-Pinazo, Encarnación (My University, 2017)
It is accepted that communication with individuals with severe intellectual disabilities is a challenging task for professionals. Technological aids have often been put forward as useful tools. A group of experts from fields such healthcare institutions within the European Project EC+ gather to created friendly communication tools with scientific information and multimodal resources to offer future professionals (university students) and professionals, tools, materials and strategies to communicate with users by means of mobile applications using agile technologies, which will improve communication and hence the quality of work of professionals and with reduce stressful situations for both groups, the disabled and worker. Precise scientific training in several syndromes that hinder communication skills, multimodal tools and the provision of friendly agile apps draws a promising picture in this particular field. https://ecplusproject.uma.es/
Keywords: Discapacitados; Aplicaciones informáticas; Technologies for communication; Disabled users; Interpreters